2013
DOI: 10.1186/1757-2215-6-36
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of miRNAs in a dihydrotestosterone-induced rat PCOS model

Abstract: BackgroundThe polycystic ovary syndrome (PCOS) is a complex and heterogeneous endocrine condition characterized by hyperandrogenism, hyperinsulinemia, insulin resistance and chronic anovulation. Regulation and interaction of a multitude of genes required for follicular development are found to be altered in PCOS. MicroRNAs (miRNAs) mediate posttranscriptional gene regulation by binding to the 3´ untranslated region of mRNAs to either inhibit or enhance translation. However, the extent and regulation of miRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 59 publications
(64 reference statements)
3
70
0
1
Order By: Relevance
“…Notably studies report (18,28) that miR-125b is similarly up-regulated by androgens in prostate cancer, and may play a crucial role in cancer cell proliferation and metastasis (29). With respect to miRs in female reproductive tissue, most work has focused on miR profiling rather than mechanism, and miR125b is reported to be one of the most abundant miRs in the ovary among different species (30,31). In fact, little is known about the expression, regulation, and function of miRs in the ovary (32).…”
Section: Nonspecific) (D-f)mentioning
confidence: 99%
“…Notably studies report (18,28) that miR-125b is similarly up-regulated by androgens in prostate cancer, and may play a crucial role in cancer cell proliferation and metastasis (29). With respect to miRs in female reproductive tissue, most work has focused on miR profiling rather than mechanism, and miR125b is reported to be one of the most abundant miRs in the ovary among different species (30,31). In fact, little is known about the expression, regulation, and function of miRs in the ovary (32).…”
Section: Nonspecific) (D-f)mentioning
confidence: 99%
“…The authors go on to demonstrate a direct effect of miR-93 on GLUT4 and that this miRNAs is over-expressed in PCOS patients and women with insulin resistance and hypothesized that this miRNA may partially explain the overlap of these two conditions (Chen et al 2013). In a rodent PCOS model, rats were given dihydrotestosterone (DHT) to induce a PCOS-like phenotype and ~25 highly expressed miRNAs were found in both control and DHT ovaries (Hossain et al 2013). Interestingly, of the differentially expressed RNAs several were shown to be selectively expressed in theca cells (Hossain et al 2013).…”
Section: 5 Non-coding Rnas Involved In Ovarian Diseasesmentioning
confidence: 99%
“…In a rodent PCOS model, rats were given dihydrotestosterone (DHT) to induce a PCOS-like phenotype and ~25 highly expressed miRNAs were found in both control and DHT ovaries (Hossain et al 2013). Interestingly, of the differentially expressed RNAs several were shown to be selectively expressed in theca cells (Hossain et al 2013). This is an important observation as theca cells are the predominant source of elevated androgens in PCOS women and these studies provide evidence that dysregulation of miRNA expression should be further evaluated in human ovarian theca cells.…”
Section: 5 Non-coding Rnas Involved In Ovarian Diseasesmentioning
confidence: 99%
“…Further studies are needed to determine whether miRNAs play a role in the etiology of PCOS or if they are downstream effects of other PCOS risk factors. Hossain et al (2013) examined changes in miRNA expression in a rat model of dihydrotestosterone (DHT)-induced PCOS. This study found significant changes in miRNA content within follicular fluid (17 up-and 72 downregulated).…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%